Biomarkers of oxidative stress and risk of developing colorectal cancer: a cohort-nested case-control study in the European Prospective Investigation Into Cancer and Nutrition. - Leufkens, A; van Duijnhoven, F; Woudt, S; Siersema, P; Jenab, M; Jansen, E; Pischon, T; Tjønneland, A; Olsen, A; Overvad, K; Boutron-Ruault, M; Clavel-Chapelon, F; et al. (2012)
Oxidative stress has been shown to play an important role in carcinogenesis, but prospective evidence for an association between biomarkers of oxidative stress and colorectal cancer (CRC) risk is limited. The authors investigated the association between prediagnostic serum levels of oxidative stress indicators (i.e., reactive oxygen metabolites (ROM) and ferric reducing ability of plasma (FRAP)) and CRC risk. This was examined in a nested case-control study (1,064 CRC cases, 1,064 matched controls) in the European Prospective Investigation Into Cancer and Nutrition cohort (1992-2003). Incidence rate ratios and 95% confidence intervals were calculated using conditional logistic regression analyses. ROM were associated with overall CRC risk (highest tertile vs. lowest: adjusted incidence rate ratio (IRR(adj)) = 1.91, 95% confidence interval (CI): 1.47, 2.48), proximal (IRR(adj) = 1.89, 95% CI: 1.06, 3.36) and distal (IRR(adj) = 2.31, 95% CI: 1.37, 3.89) colon cancer, and rectal cancer (IRR(adj) = 1.69, 95% CI: 1.05, 2.72). When results were stratified by tertile of follow-up time, the association remained significant only in participants with less than 2.63 years of follow-up (IRR(adj) = 2.28, 95% CI: 1.78, 2.94; P-heterogeneity < 0.01). FRAP was not associated with CRC risk. In conclusion, prediagnostic serum ROM levels were associated with increased risk of CRC. However, this association was seen only in subjects with relatively short follow-up, suggesting that the association results from production of reactive oxygen species by preclinical tumors.